Aniline-Driven Liquid-Liquid Extraction for Methylamine-Water Separation: Process Simulation and Performance Evaluation - Abubakar, Abdulhalim Musa; Wali, Suleiman A; Waziri, Abubakar Yusuf; Marvin, Mahlon Kida; Ngulde, Aliyu Buba; Abubakar, Muhammad Abbagoni; Abdul, Aminullah Zakariyyah; Sarkinbaka, Zakiyyu Muhammad; Yunus, Mujahid Umar; Yusuf, Abdulghaffaar Assayyidi; Saad, Mohamed; Coto, Baudilio (Journal of Sustainable Materials Processing and Management, 2023)
Methylamines are toxic with ammonia-like odor while aniline has a fishy odor. Both aniline and methylamines affect aquatic life and water quality if present in large concentrations in water. Nevertheless, the later, with solubility of 1120 g/L is more soluble in water than the former with solubility of 3.6 g/L at 25. Based on their difference in solubilities, liquid-liquid extraction (LLE) technique can be used to separate or remove the presence of any one of the two pollutants in water. The UNIQUAC property method in Aspen Plus V8.8 was proven to be the best method for the LLE of a water-aniline-methylamine ternary mixture after a single stage partition coefficient analysis with a mixing tank. Adopting the best model for a two-stage separation using ‘Extract’ and ‘RadFrac’ Aspen Plus model units, yielded three separate product streams that are 95.5% methylamine, 86.5% aniline and 100% water. The phase boundary, diagonal tie lines and a constant boiling point of 372.505 K showcased by the ternary phase diagram demonstrated the presence of an azeotrope and the ability of the RadFrac model to separate the mixture easily. Future demonstration on how to separate numerous ternary mixtures is recommended, as the need to treat effluents of many industries containing compounds of varying solubilities may warrant the setting up of a LLE unit.